ANALISIS SEKTOR UNGGULAN SEBAGAI PENDORONG PERTUMBUHAN EKONOMI DI KABUPATEN PACITAN TAHUN 2018-2021 - Iqbal Abdul Aziz Zain (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
Abstact Economic base activities have a vital role as the main driver of economic growth in Pacitan Regency. A region is said to have a basic or superior sector if the region is able to win the intense competition between regions in the same sector so as to increase the value of exports. The purpose of this study was to determine the basic or leading sector and the underdeveloped sector in Pacitan Regency. This study uses secondary data types, namely GRDP data in Pacitan Regency and East Java Province according to ADHK 2010 Business Fields in 2018-2021. The analytical method used is Location Quotient (LQ), which is a tool to measure the specialization of the economic base or superiority in Pacitan Regency. The results showed that the most superior sectors in Pacitan Regency were five sectors, namely the agricultural, forestry and fishery sectors, the construction sector, the information and communication sector, the government administration sector, the defense and compulsory social security sector, and the education services sector. As for the most underdeveloped sectors, there are three sectors, namely the processing industry sector, the water supply sector, waste management, waste and recycling and the financial and insurance services sector.